What Is the Buzz About Iconicity? How Iconicity in Caregiver Speech Supports Children's Word Learning. Issue 4 (19th April 2021) - Perry, Lynn K.; Custode, Stephanie A.; Fasano, Regina M.; Gonzalez, Brittney M.; Savy, Jordyn D.
Abstract: One cue that may facilitate children's word learning is iconicity, or the correspondence between a word's form and meaning. Some have even proposed that iconicity in the early lexicon may serve to help children learn how to learn words, supporting the acquisition of even noniconic, or arbitrary, word–referent associations. However, this proposal remains untested. Here, we investigate the iconicity of caregivers' speech to young children during a naturalistic free‐play session with novel stimuli and ask whether the iconicity of caregivers' speech facilitates children's learning of the noniconic novel names of those stimuli. Thirty‐four 1.5‐2‐year‐olds (19 girls; half monolingual English learners and half bilingual English‐Spanish learners) participated in a naturalistic free‐play task with their caregivers followed by a test of word‐referent retention. We found that caregivers' use of iconicity, particularly in utterances in which they named the novel stimuli, was associated with the likelihood that children learned that novel name. This result held even when controlling for other factors associated with word learning, such as the concreteness and frequency of words in caregiver speech. Together, the results demonstrate that iconicity not only can serve to help children identify the referent of novel words (as in previous research) but can also support their ability to retain even noniconic word‐referent mappings.